2011
DOI: 10.1186/1471-2474-12-245
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta-analysis: cytokines in fibromyalgia syndrome

Abstract: BackgroundTo perform a systematic review and meta-analysis on cytokine levels in patients with fibromyalgia syndrome (FMS).MethodsThrough December 2010 we systematically reviewed the databases PubMed, MEDLINE, and PsycINFO and screened the reference lists of 22 review articles for suitable original articles. Original articles investigating cytokines in patients with FMS were included. Data were extracted by two independent authors. Differences of the cytokine levels of FMS patients and controls were summarized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
181
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(204 citation statements)
references
References 27 publications
13
181
0
2
Order By: Relevance
“…A review by Powell et al (2013) could not establish hypocortisolism in chronic fatigue patients, but found evidence for an attenuation of the diurnal variability of the cortisol response. A similar picture arises from review studies on the role of inflammatory, infectious, or autoimmune dysfunction in functional somatic syndromes: few differences are found, and if so, they mostly pertain to different parameters (see Borchers and Gershwin, 2015;Üç eyler et al, 2011;Blundell et al, 2015;Ishihara et al, 2013;Schwille-Kiuntke et al, 2015). Importantly, whenever a dysfunction is observed, few studies test whether the abnormalities actually cause or mediate the symptoms in question.…”
Section: Authorsmentioning
confidence: 99%
“…A review by Powell et al (2013) could not establish hypocortisolism in chronic fatigue patients, but found evidence for an attenuation of the diurnal variability of the cortisol response. A similar picture arises from review studies on the role of inflammatory, infectious, or autoimmune dysfunction in functional somatic syndromes: few differences are found, and if so, they mostly pertain to different parameters (see Borchers and Gershwin, 2015;Üç eyler et al, 2011;Blundell et al, 2015;Ishihara et al, 2013;Schwille-Kiuntke et al, 2015). Importantly, whenever a dysfunction is observed, few studies test whether the abnormalities actually cause or mediate the symptoms in question.…”
Section: Authorsmentioning
confidence: 99%
“…In a recent meta-analysis, the authors reviewed the literature that investigated cytokines in FM patients. 34 The results, …”
Section: Cytokinesmentioning
confidence: 96%
“…Behm and Associates investigated the immune role, specifically mononuclear cell cytokine production in FMS and reported lower levels of IL-5, IL-6, IL-8, IL-10 and IFN-γ [10]. Other studies have also reported alterations in the signature of cytokines in FMS [11,12]. Another study examined the peripheral benzodiazepine receptors on the leukocyte surface.…”
Section: Introductionmentioning
confidence: 99%